A study comparing the effects of vincristine with those of ionizing radiation on the root meristem of Vicia faba - Haddad, Dawne Merle (Department of Human Biology, 2020)
Vincristine and vinblastine, two closely related alkaloids are extracted from the Madagaskar Periwinkle, Vinca rosea Linn. They have been shown to be effective oncolytic agents and cause arrest of mitosis at the metaphase stage, similar to that of colchicine andcolcimid. Clinically, vincristine has been found to produce a complete remission in patients with acute leukaemia. Tumour regression in patients with Hodgkin's disease, lymphosarcoma and certain childhood solid tumours have also been reported.